The Relationship Integration of Soft Skills in Clinical Skills Courses and The Learning Outcomes of Undergraduate Midwifery Students - Yulizawati Yulizawati; Radhiyatan Mardhiyah (Journal of Midwifery, 2023)
Mastery of skills at the undergraduate level is important, because it will provide provisions for students in forming the basis of professional behavior in providing effective and comprehensive Midwifery Care for pregnant, maternity and postpartum women. Learning methods in tertiary institutions use adult learning methods (adult learning). This method has a different approach, scope, goals and strategies from education in secondary schools. Studying in tertiary institutions, especially medical and health sciences, emphasizes continuous and lifelong education. This study uses a comparative study. Bivariate analysis in the form of categorical correlative using t-test, The research population was all students of the Bachelor of Midwifery Study Program, Faculty of Medicine, Andalas University, semester III. The sample is part or representative of the population studied. Based on the statistical approach, the sample size is determined by the statistical model that will be used to test the hypothesis. In this study the statistical test that will be used is the t-test for paired data. How to take samples using total sampling. Control group students were equipped with clinical skills with knowledge, general skills and special skills. After debriefing and evaluating, the results obtained were 43.5% of students had a score range between 70-74. Attitudes (soft skill roles) that are applied to these clinical skills include intrapersonal soft skills and interpersonal soft skills. Learning outcomes for psychomotor elements with the integration of soft skills, the distribution of final grades is better